The Causes and Origins of the Ekiiti-Paraapo War - Buhari Lateef Oluwafemi (Britain International for Academic Research (BIAR-Publisher), 2023)
The Ekiiti-Paraapo War, also known as the Kiriji War, was a 16-year civil war that split the Yoruba people into two subethnic kingdoms: the Western Yoruba, which included primarily the Ibadan and Oyo-speaking Yorubas, and the Eastern Yoruba, which included the Ekiti people, the Ijesha people, the Ijebu people, and others. The study examines Ajele's leadership, the root causes of the Ekiti-Parapo War, both immediate and distant, and the strategies used by the War Chiefs. The analysis also demonstrates that Imesi-Ile served as the Civil War's focal point. Many primary and secondary sources, including books, journal articles, and other scholarly publications that are pertinent to the topic are widely consulted in this study. It also gains from the vast knowledge and wisdom of old leaders and intellectuals in the Ekiti region. According to the study's findings, the effects of the conflict caused a concentration of Yoruba people in numerous cities and towns in Yorubaland, many of which are still standing today.